2017
DOI: 10.1111/plb.12549
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of the native forage grass Trichloris crinita (Poaceae, Chloridoideae)

Abstract: Trichloris crinita is a perennial forage grass species native to arid regions of the American continent. Due to its extensive area of distribution, good forage quality and resistance to drought and grazing, this species is widely utilised as forage and for revegetation purposes in environments with low water availability. Despite its importance, genetic improvement of T. crinita has been very limited, partly as consequence of the lack of knowledge on its mode of reproduction. In the present work, we studied th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 54 publications
3
29
0
5
Order By: Relevance
“…(), conclusively demonstrated that T. crinita seeds develop sexually (i.e., through double fertilization). In addition, pollination experiments performed in both studies concluded that T. crinita is self‐compatible, because all the plants analysed produced seeds under self‐pollination conditions (Gutiérrez et al., ; Kozub et al., ). In these studies, self‐pollination was ensured by isolating inflorescences in moderately transparent paper bags 2 days prior to anthesis.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…(), conclusively demonstrated that T. crinita seeds develop sexually (i.e., through double fertilization). In addition, pollination experiments performed in both studies concluded that T. crinita is self‐compatible, because all the plants analysed produced seeds under self‐pollination conditions (Gutiérrez et al., ; Kozub et al., ). In these studies, self‐pollination was ensured by isolating inflorescences in moderately transparent paper bags 2 days prior to anthesis.…”
Section: Introductionmentioning
confidence: 93%
“…The general pattern of floral development observed in this species is similar to that described for other self‐pollination grasses, including small millets (Gupta, Sood, Agrawal, & Bhatt, ) and many Australian native grasses (Whalley, Chivers, & Waters, ). Dense inflorescences and profuse flowering, as reported in T. crinita (Kozub et al., ), are believed to favour selfing and probably cause a certain amount of spontaneous self‐pollination by geitonogamy (Barrett, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several seeds of both Onosma species showed larger P ind values, with the mean P ind = 3.22 for O. arenaria and 2.98 for O. pseudoarenaria. (42,(65)(66)(67)(68)). This is the first study evaluating the genome composition in ACAs and associating the genome composition with the FCSS results.…”
Section: Fcss Data Correspond To the Models Of Chromosome Inheritancementioning
confidence: 99%